Development and Challenge of Reducer for Electric Wheel Drive Electric Vehicle - Wang Yali Yao Ligang Cai Yongwu Lin Long Wang Wenjie (Jixie chuandong)
The electric wheel drive technology subverts the driving mode of the traditional automobile and represents the development direction of the electric vehicle in the future. In particular，the electric wheel with reducer has great development potential due to its compact structure，large output torque，high efficiency and specific power. The concept，working principle，technical characteristics and suitable types of the reducer（wheel side reducer and wheel hub reducer）for electric wheel drive electric vehicles are described. The present situation of application and research of wheel side reducer and wheel hub reducer at home and abroad are briefly introduced. The performance indexes and suggestions for the type of reducer of three kinds of common electric wheel deceleration drive vehicles are given. The common problems hindering the development of wheel side reducer and wheel hub reducer are summarized，and the corresponding solutions are summarized for the bottleneck problems of wheel side reducer development. The future development direction and challenges of wheel side reducer and wheel hub reducer are prospected.